Controversies Surrounding Quality Measurement in Colon and Rectal Surgery - O'Brien, Brendan S.; McNally, Michael P.; Duncan, James E. (Clinics in Colon and Rectal Surgery, 2014)
Quality improvement in health care has become a major topic of discussion among health care providers, patients, insurance companies, and the government. National Surgical Quality Improvement Project (NSQIP), along with a multitude of other programs, exists in an attempt to create objective data that can be used to compare hospitals and providers against a national average. Studies have shown that despite good patient care and proper surgical technique, patients who undergo procedures such as colectomy have a higher incidence of surgical site infection (SSI) and other morbidities. Therefore, hospitals with a large volume of colon and rectal surgery cases are routinely identified as “high outliers” in these quality improvement programs. Programs, such as NSQIP, may not be the best way to measure quality in specific subspecialties such as colon and rectal surgery.
Keywords: NSQIP; quality improvement; colon and rectal surgery